2019
DOI: 10.1007/s10530-019-02113-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the establishment success, response to competition, and community impact of invasive and non-invasive Gambusia species

Abstract: How an invader responds to the novel biotic elements of a new community will affect its ability to invade. Species that are able to cope well with novel competitors might be expected to achieve greater establishment success. We compared the population-level responses of two mosquitofish species, the widespread invader Gambusia affinis and non-invasive G. geiseri to competition from each other and a non-invasive competitor. We simulated the invasion of a simplified pond community by introducing different combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…Consistent with the differences in temperature tolerance, only G. affinis and G. holbrooki successfully established populations in standardized pond communities in the long term while in contrast, G. geiseri and G. hispaniolae failed to establish because they suffered 100% overwintering mortality. A previous study has shown that G. affinis and G. holbrooki are also able to successfully invade pond communities in the presence of a native competitor (Rehage et al 2019). These results support the notion that the ability to cope with the abiotic conditions of target communities has a major effect on whether or not invaders become established, with life-history differences playing an important, but secondary role (Moyle and Light 1996, Hayes and Barry 2008, Bomford et al 2010, Alofs and Jackson 2015, Murphy et al 2015.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with the differences in temperature tolerance, only G. affinis and G. holbrooki successfully established populations in standardized pond communities in the long term while in contrast, G. geiseri and G. hispaniolae failed to establish because they suffered 100% overwintering mortality. A previous study has shown that G. affinis and G. holbrooki are also able to successfully invade pond communities in the presence of a native competitor (Rehage et al 2019). These results support the notion that the ability to cope with the abiotic conditions of target communities has a major effect on whether or not invaders become established, with life-history differences playing an important, but secondary role (Moyle and Light 1996, Hayes and Barry 2008, Bomford et al 2010, Alofs and Jackson 2015, Murphy et al 2015.…”
Section: Discussionsupporting
confidence: 81%
“…Notably, Sagouis et al (2015) found that, at a global scale, non-native fish species affect native freshwater fish community isotopic niches. Considerable dietary niches overlap between native and invasive species can lead to native species' niche displacement, commonly toward less preferred prey (Bøhn et al, 2008;Rogosch & Olden, 2020;Schopt Rehage et al, 2020). For example, Wainright et al (2021) found that the introduction of the invasive lake trout (Salvelinus namaycush) displaced native fishes' dietary niche in Rocky Mountain lakes.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, conservation biological control strategies would benefit from a quantitative measure of the resistance by autochthonous and allochthonous species against recently established invaders, thus enabling the identification of meaningful conservation targets (Frost et al 2019). Indeed, invaders' success can vary greatly depending on the structure of invaded food webs (Dzialowski et al 2007;Jackson et al 2013;Smith-Ramesh et al 2017;Vonesh et al 2017), through mechanisms of biotic resistance by competitors (competitive resistance) and predators (consumptive resistance) (Britton 2012;Alofs and Jackson 2014;Smith-Ramesh et al 2017;Rehage et al 2019). However, field studies comparing consumptive and competitive resistance at the whole food web level are lacking (Alofs and Jackson 2014).…”
Section: Introductionmentioning
confidence: 99%